Coherence of Surah Al-‘Alaq Verses and Their Relevance to Modern Literacy - Rosihan Anwar; M. Hafiz Fathony; Muhamad Raj Chandra; M. Mahbub Al Basyari; Idham Kholid (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
The digital transformation and paradigm shifts in 21st-century education demand a reinterpretation of the concept of literacy from an Islamic perspective. Surah Al-‘Alaq, as the first revealed chapter, contains fundamental messages related to the activities of reading, thinking, and learning, which carry both spiritual and epistemological values. This study aims to analyze the coherence (munasabah) among the verses in Surah Al-‘Alaq verses 1–5 and to explore their relevance to the concept of modern literacy. The method employed is the Systematic Literature Review (SLR) with a qualitative descriptive approach, involving thematic analysis of 25 sources—consisting of scholarly journals and classical as well as contemporary tafsir—published in the last five years. The findings show that the structure of verses in Surah Al-‘Alaq forms an integrative Qur’anic literacy framework, encompassing spiritual dimensions (reading in the name of God), existential dimensions (awareness of creation), epistemological dimensions (the use of the pen as a symbol of civilization), and transformational dimensions (the process of continuous learning). These values are strongly relevant to modern literacy, such as digital, critical, and ethical literacy. Surah Al-‘Alaq can serve as a foundation for developing an Islamic literacy paradigm that meets contemporary challenges. The implication is that Islamic education needs to design a literacy curriculum that not only focuses on technical skills but also on shaping the spiritual, moral, and intellectual character of learners.